Interpreting and translating in Nazi concentration camps during World War II - Tryuk, Malgorzata (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2016)
This article investigates translation and interpreting in a conflict situation with reference to the Nazi concentration camps during World War II. In particular, it examines the need for such services and the duties and the tasks the translators and the interpreters were forced to execute. It is based on archival material, in particular the recollections and the statements of former inmates collected in the archives of concentration camps. The ontological narratives are compared with the cinematic figure of Marta Weiss, a camp interpreter, as presented in the docudrama “Ostatni Etap”(“The last Stage”) of 1948 by the Polish director Wanda Jakubowska, herself a former prisoner of the concentration camp. The article contributes to the discussion on the role that translators and interpreters play in extreme and violent situations when the ethics of interpreting and translation loses its power and the generally accepted norms and standards are no longer applicable.